Characterizing the toxic gaseous emissions of gasoline and diesel vehicles based on a real-world on-road investigation. (1st March 2021) - Zhang, Lanyi; Lin, Jane; Qiu, Rongzu
Abstract: The increasing production and population of motor vehicles in China have severely aggravated ambient air pollution and threatened public health, as vehicle emissions generate toxic pollutants. Understanding vehicular emission characteristics for the purpose of targeted control measures is critically important for improving efficient use of fossil energy and promoting sustainable development of global ambient environment. There have been many studies on vehicle emissions in cities of a level terrain (i.e., road grade within 2%), while there is currently very limited research effort in studying vehicle emissions in mountainous terrains. In China, mountains, plateaus, and hilly areas account for 69% of the total land area. To fill that knowledge gap, this study performed real-world emission measurements on a busy mountainous road in a Chinese city, Fuzhou, using both light-duty gasoline and medium-duty diesel vehicles equipped with a Portable Emissions Measurement System. Instantaneous second-by-second CO, NOx, and HC emissions, vehicle speed, and location data were recorded simultaneously. There are several major findings and policy implications from the study. First, per kilometer emissions from the medium-duty diesel vehicles are orders of magnitude higher than the light-duty gasoline vehicles, and therefore vehicle emission control policy must emphasize on medium-duty diesel vehicles to achieve greater reduction. Second, the effects of speed and acceleration, separate or joint, on per kilometer emissions are nonlinear and differ between the light-duty gasoline and the medium-duty diesel vehicles in the mountainous road. Third, moderate upgrade, acceleration, and moderately high speed are found to be associated with high per kilometer emissions in mountainous roads. Conservative driving behavior associated with steep uphill actually results in slightly reduced per kilometer emissions from those with moderate uphill driving. Fourth, with the Chinese national vehicle emission standards become more stringent, there is a lag in the vehicular emissions control technology development and regulations for NOx and HC as compared to CO in China. And lastly, per kilometer emissions of light-duty gasoline vehicles are more sensitive to vehicle specific power than those of medium-duty diesel vehicles. And the current MOVES operating mode definition by vehicle specific power is not adequate for medium-duty diesel vehicle emissions in mountainous roads. Thus, a modified operating mode definition is proposed. The study findings will provide important scientific basis for developing a China-specific mountainous emissions model and vehicle emission control policies. Highlights: Gaseous vehicular emissions are measured in real time in Chinese mountainous terrain. CO emissions show large reductions with the newer and more stringent emission standards. The newer model year vehicles have higher HC emissions. Modified VSP bins are proposed toward building a China emission model. Recommendations for policy and practice have been proposed according to the results.